45 ROLE OF INTERFERON-γ-INDUCIBLE PROTEIN 10 IN THE PATHOGENESIS OF COXSACKIEVIRUS B3. Issue 1 (1st January 2007) - Shier, C.; Yuan, J.; Lim, T.; Yang, D. C.
Abstract : Background: Coxsackievirus B3 (CVB3) is the primary cause of viral myocarditis. It exerts its effects on its host by altering the cellular gene expression involved in viral replication, viral clearance, and maintenance of host immunity. Among the genes that are up-regulated is IP10, which is a potent chemoattractant of T cells. Our goal is to investigate the role of IP10 in the pathogenesis of CVB3-induced myocarditis using both IP-10 transgenic and knockout mouse models. Hypothesis: IP10 is required for proper host immune response against CVB3 infection and knocking out IP10 delays virus clearance by causing insufficient recruitment of activated TH 1 lymphocytes toward the infection. Conversely, too much IP10 causes overstimulation of the immune response; thus, overexpression of IP10 will result in a more severe myocarditis. Methods: Four to 5-week-old IP10 transgenic (Tg), knockout (KO), and wild-type (WT) mice were infected with 10 5 pfu CVB3 by intraperitoneal injection. Their hearts were collected at 7 days postinfection (pi) and were analyzed for viral replication by plaque assay and for severity of immune response by using immunohistochemistry (IHC). Furthermore, quantitative RT-PCR (qRT-PCR) was performed to characterize the expression of chemokines and cytokines related to IP10 that might be involved in determining the myocarditis severity. Results: The IHC results demonstrated a close relationship between IP-10 expression and degree of T cell infiltration, suggesting that IP10 plays a critical role in the physiologic response of activated T-cell recruitment to the heart following CVB3 infection. By qRT-PCR, mRNA of TNFα (proinflammatory cytokine), IFN-inducible T-cell alpha chemoattractant (I-TAC, CXCL11), and TH 1 cytokines (IFN-γ, IL-12α), but not TH 2 cytokines (IL-4, IL-5), were found to show a lower level of expression in CVB3-infected KO mice compared with the control WT mice, suggesting mainly that the TH 1 immune response was impaired in IP10 KO mice. At day 7 pi, there was no difference in the virus titer of the hearts in Tg, KO, and WT mice, but we expect that a difference may be detectable at day 10 pi. Conclusion: IP10 KO mice infected with CVB3 may have an impaired ability to control viral clearance in the heart, which is associated with decreased recruitment of TH 1 lymphocytes into the heart and reduced levels of IFN-γ and therefore decreased I-TAC expression in the heart. IP10 Tg mice, on the other hand, may have an excessive immune response and a more severe myocarditis.